2014
DOI: 10.3390/v6103778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacteriophage Infection in Combination with Tobramycin on the Emergence of Resistance in Escherichia coli and Pseudomonas aeruginosa Biofilms

Abstract: Bacteriophage infection and antibiotics used individually to reduce biofilm mass often result in the emergence of significant levels of phage and antibiotic resistant cells. In contrast, combination therapy in Escherichia coli biofilms employing T4 phage and tobramycin resulted in greater than 99% and 39% reduction in antibiotic and phage resistant cells, respectively. In P. aeruginosa biofilms, combination therapy resulted in a 60% and 99% reduction in antibiotic and PB-1 phage resistant cells, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 32 publications
5
77
2
Order By: Relevance
“…Changes in DNA replication could induce disruption of the biofilm exopolymeric matrix causing increased penetration of phage and antibiotic at higher diffusion rates. Similar mechanisms have been previously reported in the study of amikacin and phage synergism [40] as well as tobramycin (0.5 µg/ml) and 0.01 MOI phage for the treatment of established P. aeruginosa biofilms [49]. Hagens et al show that phage treatment augmented inhibition of P. aeruginosa using low doses of tetracycline [50].…”
Section: Discussionsupporting
confidence: 55%
“…Changes in DNA replication could induce disruption of the biofilm exopolymeric matrix causing increased penetration of phage and antibiotic at higher diffusion rates. Similar mechanisms have been previously reported in the study of amikacin and phage synergism [40] as well as tobramycin (0.5 µg/ml) and 0.01 MOI phage for the treatment of established P. aeruginosa biofilms [49]. Hagens et al show that phage treatment augmented inhibition of P. aeruginosa using low doses of tetracycline [50].…”
Section: Discussionsupporting
confidence: 55%
“…Phage therapy is being considered, again, for use both in the food industry and in medicine (25). In addition, several reports showed that phage therapy improved (26)(27)(28), and in some cases was even more successful than (29,30), antibiotic treatment.…”
mentioning
confidence: 99%
“…Additionally, phage-encoded proteins, such as endolysins and exopolysaccharide depolymerases, can also be used for biofilm removal (19)(20)(21). Nevertheless, most studies available to date have focused on single-species communities, while only limited work has tackled the elimination of polymicrobial biofilms with phage-based products (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%